EMS-effect of Exercises with Music on Fatness and Biomarkers of Obese Elderly Women - Kim, Jiyoun; Jee, Yongseok (Medicina (Kaunas, Lithuania), 2020)
Background and objectives: Electromyostimulation (EMS) has been shown to improve body composition, but what biomarkers it affects has not been investigated. The purpose of this study was to compare the EMS-effect of exercises with music on fatness and biomarker levels in obese elderly. Materials and Methods: Twenty-five women were randomly classified into a control group (CON) and EMS group (EMSG). EMS suits used in this study enabled the simultaneous activation of eight pairs with selectable intensities. Program sessions of EMS were combined with exercises of listening to music three times a week for eight weeks. Although both groups received the same program, CON did not receive electrical stimuli. Results: Compared with CON, a significant effect of the EMS intervention concerning decreased fatness, as well as an increased skeletal muscle mass and basal metabolic rate, were evident. Tumor necrosis factor-a, C-reactive protein, resistin, and carcinoembryonic antigen of biomarkers were significantly different in the groups by time interaction. Similarly, the positive changes caused by EMS were represented in lipoprotein-cholesterols. Conclusions: The results indicate that a significant effect due to the EMS intervention was found concerning body composition and biomarkers in obese elderly women.